2021
DOI: 10.1139/cjas-2020-0184
|View full text |Cite
|
Sign up to set email alerts
|

Effects of broiler chicks fed the low crude protein diet supplemented with Achyranthes japonica Nakai root extract on growth performance and carcass traits

Abstract: A total of 360 1-day-old broiler chicks were randomly assigned to 4 treatments with 5 replicate cages and 18 birds per cage for a 35-day trial to investigate the effects of supplementing Achyranthes Japonica Nakai (AJN) root extract in low crude protein (CP) diet on growth performance and carcass traits. Experimental diets were divided as standard CP content diet, low CP content (LCP) diet, and LCP diet supplemented with 0.025 or 0.050% AJN root extract. Dietary CP reduction impaired growth performance and car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Our results suggested that AJE (0.025% and 0.050%) supplementation reduces the pH level compared to the control diet along with SCP and LCP, which has an overall effect on meat quality. Dang et al [ 27 ] reported that supplementation of AJE to the diet had no positive effect on carcass quality. Interestingly, in our study, we found a lower pH level with AJE supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggested that AJE (0.025% and 0.050%) supplementation reduces the pH level compared to the control diet along with SCP and LCP, which has an overall effect on meat quality. Dang et al [ 27 ] reported that supplementation of AJE to the diet had no positive effect on carcass quality. Interestingly, in our study, we found a lower pH level with AJE supplementation.…”
Section: Discussionmentioning
confidence: 99%